Catching Christmas [large type] - Blackstock, Terri, 1957- (Center Point Large Print, 2018)
"New York Times bestselling author Terri Blackstock tells the rich and heartwarming story of a cab driver, a young attorney, and the elderly woman who will stop at nothing to give her granddaughter one special gift for Christmas"--